Exploring the potential of taro (Colocasia esculenta) starch: Recent developments in modification, health benefits, and food industry applications - Rakesh Kumar Gupta; Proshanta Guha; Prem Prakash Srivastav (Food Bioengineering, 2024)
Abstract Taro is a tropical plant and an underutilized root crop that has a good source of carbohydrate. Taro tuber contains 70%–80% of starch on dry basis. This review highlights the extraction of taro starch, latest advancements in the modification such as physical, chemical and enzymatic modification of taro starch. Furthermore, after modification of taro starch, molecular weight and amylopectin branch chain length distribution, granular shape, percentage crystallinity, swelling and solubilization, pasting and thermal properties and in vitro digestibility of taro starch were significantly affected. Additionally, researchers have explored novel methods to modify the physicochemical characteristics of taro starch, enhancing its functionality as a thickening, gelling, and stabilizing agent in various food formulations. However, fabrication of nanoparticles from taro starch was also studies. Various health benefits of taro starch have been reported in this study. One significant health benefit of taro starch is its potential to improve blood sugar management. Furthermore, the versatility of taro starch in food applications has expanded, ranging from traditional staples to modern convenience foods. Its gluten‐free nature makes it an attractive option for individuals with gluten sensitivity or celiac disease. Taro starch is increasingly incorporated into bakery products, snacks, noodles, and as a thickening agent in soups and sauces. The unique sensory attributes and nutritional profile of taro starch contribute to the development of novel, health‐conscious food products that cater to evolving consumer preferences.